If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m(x) = x + 1 Multiply m * x mx = x + 1 Reorder the terms: mx = 1 + x Solving mx = 1 + x Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by 'x'. m = x-1 + 1 Simplifying m = x-1 + 1 Reorder the terms: m = 1 + x-1
| 240=12x+4y | | 250/130xx= | | 7w^2+2w-2=0 | | 10x^2+59x-6=0 | | 10x-8x=11 | | 6q^2-q=0 | | 3y-1=23 | | 180/n=63-51 | | -5/9-(-5/9)= | | -12x+48=3x-72 | | 3(9s+3)-19s=2(4s+6)-13 | | 3x+8y-7z=0 | | g^2-6=0 | | 2x+30+4x+2x+10=180 | | -2x^2=7x | | -8=x+5-1 | | 0.2-x=0.04 | | 5=9w+8 | | 3(-10)=2(2(-10)+7) | | 100+x^2=0 | | 12p+3=104 | | 3m+zr=r-7g | | 2xcos(2x)-x^2+4x-4=0 | | 2/5(6a-3)=1/7(5-9)-2 | | -2.2-m=13.2 | | -2.2-m=13.32 | | -2.2-m=13.3 | | A(n)=5+(n-1)6 | | 25x-21=11x | | 2.9q-4.7-5.6q=-1.7q-4.7 | | .875x-y=0 | | 8x+9-5x-15=0 |